2016
DOI: 10.1016/j.ebcr.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Praxis-induced reflex seizures mainly precipitated by writing due to a parietal focal cortical dysplasia

Abstract: We report the case of a 23-year-old left-handed woman with medically intractable praxis-induced reflex seizures mainly precipitated by writing. Selective resection of subtle end-of-sulcus cortical dysplasia in the right inferior parietal lobule resulted in freedom from seizures. To the best of our knowledge, this is the first case of praxis-induced reflex seizures mainly precipitated by writing in which a focal lesion was found and treated successfully by surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Several studies suggest that the underlying mechanism of writing epilepsy may generate presumably from the left frontal lobe (4,10), but an abnormality in the parietal lobe, observed on functional imaging may play an important role in reducing the threshold of epileptiform discharges. For instance, a study by Racicot et al (14) reported that their patient experienced reflex seizures which was precipitated mainly due to writing and focal cortical dysplasia in the inferior parietal lobe. The focal cortical dysplasia in this patient was correlated with hypometabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggest that the underlying mechanism of writing epilepsy may generate presumably from the left frontal lobe (4,10), but an abnormality in the parietal lobe, observed on functional imaging may play an important role in reducing the threshold of epileptiform discharges. For instance, a study by Racicot et al (14) reported that their patient experienced reflex seizures which was precipitated mainly due to writing and focal cortical dysplasia in the inferior parietal lobe. The focal cortical dysplasia in this patient was correlated with hypometabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature indicate that the possible causes of reflex writing epilepsy include focal cortical dysplasia (14) inherit traits of seizures (9) and prior history of epilepsy (9,10,14,17). Usually, myoclonic seizures of one or both hands are precipitated by writing, which can rapidly develop into systemic myoclonus or focal to bilateral tonic-clonic seizure (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSs triggered by praxis, calculating, reading-writing or language, suggest the epileptic readiness of high-level, complex networks producing bilateral ictal myocloni and EEG patterns in several such cases (Pt 13) [6,7,23,24,27,[39][40][41][42]45]. These patients' seizure-symptoms -ictal facial twitches or alexia -point to the wide-spread reading-speaking system [6,27].…”
Section: High Level Complex Stimuli -"Praxis-induced Rss"mentioning
confidence: 99%
“…One way to classify RSs follows the type of the evoking stimuli: sensory or cognitive, simple or complex [7,[12][13][14][15][16][17][18][23][24][25][26][27][28][29][30][31]. Another classification follows the supposed focal (unilateral) or generalised (bilateral from the beginning) nature of seizures with some hints that even bilateral RSs might represent secondary and quickly spreading unilateral (focal) ones [1,19,20].…”
Section: Introductionmentioning
confidence: 99%